2021
DOI: 10.11606/s1518-8787.2021055003478
|View full text |Cite
|
Sign up to set email alerts
|

Attitude and perception towards vaccination against poliomyelitis in Peshawar, Pakistan

Abstract: OBJECTIVE: This research aimed to quantitatively assess the general public's awareness, attitude and perception of polio and its vaccination in Peshawar KPK, Pakistan. METHODS: We conducted a survey-based study to understand the surge in polio cases from 2015 to 2019 in the Peshawar city of the Khyber Pakhtunkhwa (KPK), Pakistan. A pre-tested questionnaire-based study was conducted in 2019 to assess the attitude and general perception of residents of Peshawar KPK towards polio vaccination. RESULTS: Out of 241 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…19 The present study did not find any association between knowledge regarding polio and its immunization and the gender of the parents. The results of this study are concordant with the findings of Shafique et al 18 However, Khan et al 20 found that poor uptake of polio vaccines was associated with illiteracy, socioeconomic status, and women empowerment. In the current study, a positive association of knowledge and attitude with the skilled occupation of fathers (p value 0.01 and 0.018, respectively) was observed.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…19 The present study did not find any association between knowledge regarding polio and its immunization and the gender of the parents. The results of this study are concordant with the findings of Shafique et al 18 However, Khan et al 20 found that poor uptake of polio vaccines was associated with illiteracy, socioeconomic status, and women empowerment. In the current study, a positive association of knowledge and attitude with the skilled occupation of fathers (p value 0.01 and 0.018, respectively) was observed.…”
Section: Discussionsupporting
confidence: 91%
“…It was found that urban residence, level of education of both parents, higher income, and having a skilled job, were associated with adequate knowledge (p < 0.05). Parents with higher incomes have greater access to knowledge and vaccinations as reported by Shafique et al 18 from another study from Pakistan.…”
Section: Discussionmentioning
confidence: 73%
“…As described in the Health Belief Mode, the preventive actions, like getting a vaccination, depend on how people see the risks of disease and how they perceive the effectiveness, benefits, and costs of these actions 25 . Pakistan and Afghanistan are two countries where nation-wide immunization has always been challenging as we have seen in the case of polio eradication program according to Shafique et al 26 (2021). In this study it was initially decided to contact maximum number of viral hepatitis patients residing in the study area.…”
Section: Discussionmentioning
confidence: 99%